EVALUATION OF RADIOACTIVE EQUILIBRIUM STATES OF RADIONUCLIDESA IN THE URANIUM DECAY CHAIN - Muzafarova Dilsora Hamid qizi; Soliyev Tursunboy Izzatillo o‘g‘li (Web of Journals Publishing, 2025)
This article investigayes the factors that cause disturbances in radioactive equilibrium with in the uranium decay chain. Numerous nuclear-physical factors influence the violation of radioactive equilibrium, the most significant of which is the heat energy released by the multiple radioisotopes formed from the parent ore. Additionally, relationships among atomic mass number, half-life, decay energy, radioactive equilibrium coefficient and nuclear decay constants of radionuclides in the uranium decay chain are analyzed.
Keywords: Uranium radionuclide chain, radioactive equilibrium, half-life, radioactive equilibrium coefficient, nuclear decay constants.